The company [videorecording (DVD)] - O'Donnell, Chris; Molina, Alfred, 1953-; Keaton, Michael, 1951-; Salomon, Mikael, 1945-; Littell, Robert, 1935- (Sony Pictures Home Entertainment, 2007)
Depicts the global power struggle between the U.S. and the Soviet Union, told from the viewpoint of CIA and KGB spies. Spans four decades, from the dawn of the Cold War in the 1950s to the downfall of the Soviet Union in the '90s. Trace the activities of the CIA's underground fight with the KGB and where three CIA agents must find out the moles in their own ranks before every operation in an unrelenting battle within the organization itself.